2021
DOI: 10.1007/s00520-021-06209-6
|View full text |Cite
|
Sign up to set email alerts
|

Paired exercise has superior effects on psychosocial health compared to individual exercise in female cancer patients

Abstract: Purpose Exercise improves the quality of life (QOL) in cancer patients recovering from treatment. Since group exercise fosters cohesion, we sought to determine if paired exercise would have similar, positive effects. An experiential study design was used to compare the effect of exercise (12 weeks) on psychosocial health in paired versus individually trained cancer patients. Methods Female cancer patients ( n = 28) who completed cancer treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“… 39 Physical exercise reduces the risk of depressive symptoms in cancer patients because it improves immune function and relieves patients’ anxiety and tension; this further improves sleep and appetite, promotes digestion and increases the body’s tolerance to pain. 40 , 41 Using a mouse model, Crupi et al. showed that brain inflammation, impairment and hippocampal plasticity are associated with anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Physical exercise reduces the risk of depressive symptoms in cancer patients because it improves immune function and relieves patients’ anxiety and tension; this further improves sleep and appetite, promotes digestion and increases the body’s tolerance to pain. 40 , 41 Using a mouse model, Crupi et al. showed that brain inflammation, impairment and hippocampal plasticity are associated with anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who undergo 12 weeks of exercise training, following the exercise recommendations for this specific population [ 34 ], have improved fitness, health and psychosocial outcomes [ 35 , 36 ]. They report that they “feel stronger, more coordinated,” and they “have more energy and sleep better” [ 20 ]. Reduced medication use, improved mood, and return to ADLs reduces the burden on the health care system, emotionally as well as financially.…”
Section: Societal Impactsmentioning
confidence: 99%
“…Not surprisingly, exercise itself has the same boosting effect on mood [ 44 , 45 , 46 , 47 ]. The socialization associated with exercise may have powerful [ 21 ] or even synergetic benefits on well-being [ 20 ]. Not only does exercise help patients to feel more connected and reintegrate into a society from which they had been isolated (especially in patients with limited mobility), but this feeling of community benefits all who are involved, including program administrators, faculty and interns.…”
Section: Societal Impactsmentioning
confidence: 99%
See 2 more Smart Citations